Employment and macroeconomic variables: evidence from Malaysia, Philippines and Singapore - Norazlina, Abdullah; Yasmiza, Long; Zalina, Abu Naim (2011)
This study examines the meaningful relationship between employment and macroeconomic variables such as domestic capital, gross domestic product and government expenditure in three major ASEAN economies, namely Malaysia, Singapore and Philippines. Johansen (1991) cointegration method coupled with VECM (vector-error-correction model) testing procedure is employed to analyze the impact of the selected variables. The period of interest is 1970-2005 using annual data. The empirical results demonstrate mixed results whereby though cointegration could be detected for all three countries; in the case of Malaysia, the causality that could be detected are, capital granger causes employment and employment granger causes government expenditure, as for Singapore, trade granger causes capital and lastly for the case of Philippines, both income and trade granger causes government expenditure.